2022
DOI: 10.2807/1560-7917.es.2022.27.16.2200250
|View full text |Cite|
|
Sign up to set email alerts
|

Vaccine-induced and naturally-acquired protection against Omicron and Delta symptomatic infection and severe COVID-19 outcomes, France, December 2021 to January 2022

Abstract: We assessed the protection conferred by naturally-acquired, vaccine-induced and hybrid immunity during the concomitant Omicron and Delta epidemic waves in France on symptomatic infection and severe COVID-19. The greatest levels of protection against both variants were provided by hybrid immunity. Protection against Omicron symptomatic infections was systematically lower and waned at higher speed than against Delta in those vaccinated. In contrast, there were little differences in variant-specific protection ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 12 publications
8
26
0
Order By: Relevance
“…We found that among 2-dose vaccine recipients, recent prior Delta infection was associated with higher protection against severe disease from Omicron, but small case numbers precluded equivalent comparisons among individuals who received a third vaccine dose. Our findings regarding hybrid immunity are consistent with some other studies of vaccine effectiveness [23] , [24] , [25] and immune response to vaccination and infection [26] , [27] which suggest each vaccine dose and/or infection with SARS-CoV-2 can provide incremental improvements in protection against subsequent severe disease over time. However as indicated by the World Health Organization, [28] in order to optimise future use of vaccines, more data is required to better understand how differences in the variant that individuals were infected with, and the number, timing and type of vaccine dose, may affect subsequent infection risk.…”
Section: Discussionsupporting
confidence: 91%
“…We found that among 2-dose vaccine recipients, recent prior Delta infection was associated with higher protection against severe disease from Omicron, but small case numbers precluded equivalent comparisons among individuals who received a third vaccine dose. Our findings regarding hybrid immunity are consistent with some other studies of vaccine effectiveness [23] , [24] , [25] and immune response to vaccination and infection [26] , [27] which suggest each vaccine dose and/or infection with SARS-CoV-2 can provide incremental improvements in protection against subsequent severe disease over time. However as indicated by the World Health Organization, [28] in order to optimise future use of vaccines, more data is required to better understand how differences in the variant that individuals were infected with, and the number, timing and type of vaccine dose, may affect subsequent infection risk.…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, the combination of vaccine-induced and natural immunity provides more complete protection against SARS-CoV-2 infection and severe outcomes. Other authors have also reported that hybrid immunity from previous infection and recent booster vaccination conferred the strongest protection [1,2,13,14,17].…”
Section: Discussionmentioning
confidence: 89%
“…Preclinical studies with hamsters show that intranasal challenge with the ancestral Wuhan strains results in 100% seroconversion and protects from subsequent reinfection by the Delta VOC 55 . Several observational studies profiling millions of humans support that hybrid immunity (one or more doses of vaccines and infection) is superior to two or even three doses of vaccines in preventing severe infection/hospitalization with emerging variants 56-58 . The superiority of hybrid immunity has been documented when the primary infection was with the Delta VOC, and now, more recently, with the Omicron VOC 59-62 .…”
Section: Discussionmentioning
confidence: 99%